The shape and frequency of Edgeworth price cycles in an Australian retail gasoline market - Bloch, Harry; Wills-Johnson, Nick (Centre for Research in Applied Economics, Curtin Business School, 2010)
Gasoline prices in many markets follow a saw-toothed pattern known as an Edgeworth Cycle. Lewis (2009) introduces a novel way of measuring the shape of the cycle, the median change in price, and regresses this against a number of explanatory variables in US markets. Here, we undertake a similar regression analysis, but using data from Perth, Australia, and with a novel measure of market structure as a regressor. We also explore a novel measure, based on spectral analysis, of the use of cycles in a mixed strategy, and the factors which drive this use.